A numerical study of the propagation of organic gellant-based fuel-rich premixed spray flames. (September 2016) - Greenberg, JB; Kagan, LS; Sivashinsky, GI
The behavior of laminar rich, organic gellant-based premixed spray flames is investigated for the first time. The pulsating evaporation of such spray droplets, that has been observed experimentally, is accounted for. The numerical investigation discloses two main important findings. First, the phenomenon of the creation of flame hot-spots in organic gellant-based spray diffusion flames, associated with the pulsating evaporation, is absent in the premixed flame context. Second, the influence of the temperature of onset of the pulsations and their frequency on the propagation velocity of premixed gel spray flames was examined. These parameters were found to impact on whether the flame front moves steadily through the initial pre-mixture or whether it exhibits oscillations in its movement.